Numerical Models for Hydraulic Refracturing on Vertical Oil Wells - Bratov, Vladimir (International Journal of Engineering and Technology, 2018)
The paper presents an approach for simulation of refracturing treatment on vertical oil wells. The model is accounting for filtration of hydraulic fracturing fluid through the proppant packed inside the crack formed during previous hydraulic fracturing treatments. The simulations provide a possibility to estimate history of stress intensity factor appearing at the tip of the existing crack once the time profile of pressure within the wellbore is given. Introducing critical value of the stress intensity factor for the fractured media, time-to-fracture initiation (after pressure increase start) can be estimated and compared to instance of fracture event registered in real conditions. Also, the possibility of fracture reorientation through formation of new fractures at the region adjacent to the wellbore is studied.Â